Advances of human bone marrow-derived mesenchymal stem cells in the treatment of cartilage defects: A systematic review. (June 2014) - Gopal, Kaliappan; Amirhamed, Haji Alizadeh; Kamarul, Tunku
Mesenchymal stem cell (MSC)-based therapies represent a new option for treating damaged cartilage. However, the outcomes following its clinical application have seldom been previously compared. The present paper presents the systematic review of current literatures on MSC-based therapy for cartilage repair in clinical applications. Ovid, Scopus, PubMed, ISI Web of Knowledge and Google Scholar online databases were searched using several keywords, which include "cartilage" and "stem cells". Only studies using bone marrow-derived MSC (BM-MSC) to treat cartilage defects clinically were included in this review. The clinical outcomes were compared, and the quality of the tissue repair was analysed where possible. Of the 996 articles, only six ( n  = 6) clinical studies have described the use of BM-MSC in clinical applications. Two studies were cohort observational trials, three were case series, and one was a case report. In the two comparative trials, BM-MSCs produced superior repair to cartilage treatment without cells and have comparable outcomes to autologous chondrocyte implantation. The case series and case–control studies have demonstrated that use of BM-MSCs resulted in better short- to long-term clinical outcomes with minimal complications. In addition, histological analyses in two studies have resulted in good repair tissue formation at the damaged site, composed mainly of hyaline-like cartilage. Although results of the respective studies are highly indicative that BM-MSC-based therapy is superior, due to the differences in methods and selection criteria used, it was not possible to make direct comparison between the studies. In conclusion, published studies do suggest that BM-MSCs could provide superior cartilage repair. However, due to limited number of reports, more robust studies might be required before a definitive conclusion can be drawn.